PERAN LAYANAN INFORMASI TENTANG BAHAYA SEKS BEBAS UNTUK MENINGKATKAN PEMAHAMAN MENGENAI KESEHATAN ALAT REPRODUKSI (Penelitian Pada Remaja Di Wonosari, Jatikuwung, Gondangrejo, Karanganyar Tahun 2021) - Pramesti, Nadine Vio (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
This study aimed to determine the level of understanding of adolenscents about the dengers of free sex regarding reproductive health through information services carried out in RT 04 RW 03 Wonosari Village Jatikuwung, Gondangrejo, Karanganyar. This research is a qualitative research. The research subjects were 3 teenagers and their parents. Data obtained through observation interviews and documentation. Observations were carried out by the researcher by observing the behavior of research subjects and their enviroment. Then continued with interviews with research subjects and parents to obtain more accurate data. This is confirmed by the documentation. The validity of the data is through triangulation of sources and triangulation of techniques. Qualitative data analysis is through the following steps: data collection data, reduction data, presentation, verification. Based on data analysis it could be concluded that in Wonosari village RT 04 RW 03 Jatikuwung, Gondangrejo, Karanganyar there were 3 teenagers who still did not understand about the dangers of free sex and the health of the reproductive system. This was due to a lack of available information. After being given treatment through information services the 3 teenagers could understand it better. The conclusion of this study showed that there was an increase in understanding after the research subjects received information services. Keywords: Role of Information Services; Dangers of Free Sex; Reproductive System Health